Analysis of the Active Inertia Power provided by Grid-Forming Strategies during a RoCoF - Urtasun, Ibai; Urtasun, Andoni; Bautista, Guillermo; Marroyo, Luis (2024 International Conference on Renewable Energies and Smart Technologies (REST), 2024)
Power electronic-based generators are becoming increasingly prevalent in the electrical grid, necessitating their support in disturbances previously handled only by synchronous generators. One of the tests proposed by regulations is to evaluate the response of grid-forming inverters to a Rate of Change of Frequency (RoCoF). However, there is no detailed analysis of the effect of control parameters on the active inertia power. This article presents the temporal response equation of an inverter subject to a RoCoF and introduces the concept of equivalent inertia showing that it also depends on the damping factor. Thanks to this analysis and the flexibility of inverters, the parameter design of existing grid-forming strategies is proposed to achieve the desired active inertia power and system damping ratio. Theoretical analysis and control strategies have been validated by simulation.